2020
DOI: 10.7759/cureus.11764
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Spectrum of Primary and Metastatic Neuroendocrine Neoplasms

Abstract: Introduction Neuroendocrine neoplasms (NENs) are a heterogeneous group of tumors with histological features varying from well-differentiated neuroendocrine tumors (WDNETs) to poorly differentiated neuroendocrine carcinomas (PDNECs). In this study, we investigated the clinicomorphological spectrum of NENs including tumor grade, site of origin, and metastasis. Methods We retrospectively studied 125 cases of NENs (at the Department of Histopathology, Liaquat National Hospital and Medical College, Karachi) between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…He et al found that the prognosis varied among different types of DLBCL after the introduction of rituximab and other targeted therapies, which can be important for clinical decision-making and for individualized treatment [ 16 ]. Ki67, which is a nuclear non-histone protein and is strictly associated with cell proliferation, is being widely used to monitor numerous malignancies, including lymphoma and neuroendocrine tumors [ 9 , 17 , 18 ]. Some recent papers have confirmed that a high Ki67 proliferation index is associated with shorter overall survival [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…He et al found that the prognosis varied among different types of DLBCL after the introduction of rituximab and other targeted therapies, which can be important for clinical decision-making and for individualized treatment [ 16 ]. Ki67, which is a nuclear non-histone protein and is strictly associated with cell proliferation, is being widely used to monitor numerous malignancies, including lymphoma and neuroendocrine tumors [ 9 , 17 , 18 ]. Some recent papers have confirmed that a high Ki67 proliferation index is associated with shorter overall survival [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…They tend to arise from neuroendocrine cells, i.e., cells having characteristics of both nerve cell (ability to receive signals from the nervous system) and endocrine cells (ability to secrete hormones and peptides) [ 1 ]. Histologically, NENs are subclassified into low-proliferating well-differentiated neuroendocrine tumors (WDNETs) and high-proliferating poorly differentiated neuroendocrine carcinomas (PDNECs) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroendocrine neoplasms (NENs) are a group of tumors which develop from the neuroendocrine cell system, can involve almost all anatomical sites and present various clinical manifestations associated with the production of specific hormones [ 1 , 2 , 3 ]. Gastro-entero-pancreatic NENs (GEP-NENs) account for 70% of NENs, most commonly reported in the small bowel (38%) and rectum (34.4%), and less frequently in the esophagus or anus [ 1 , 4 ].…”
Section: ⧉ Introductionmentioning
confidence: 99%
“…Another update consists of the new defined mixed neuroendocrine non-NENs (MiNENs), former called mixed adeno-NECs (MANECs), in which neuroendocrine and non-neuroendocrine components represents each more than 30% of the tumor cells [ 2 ].…”
Section: ⧉ Introductionmentioning
confidence: 99%